A research on public opinion towards government housing policies in Kota Kinabalu / Justin Lampok and Muhammad Munawwar Assiddiq Rijal - Lampok, Justin; Rijal, Muhammad Munawwar Assiddiq (2014)
The soaring prices of houses in these few years has attracted and forced inhabitants of Kota Kinabalu city to voice out their dissatisfactions over this matter. Inadequacy of affordable housing they claimed, are one of the many problems that needed to be settled by the government from both Federal level and also from State level. Thus, in the effort of not demonizing the governments' image and helping to solve this matter, a research on the public opinion towards the Government Housing Policies was conducted. The extent of the public opinions will be assessed in this study with the help of 147 samples.